PROJEK PEMBUATAN FILM MELALUI MODEL PEMBELAJARAN PROJECT BASED LEARNING DAN MODEL PENGEMBANGAN 4D - Abdul Latif; Asdar Asdar; Herlina Ahmad; Ainun Rahimah; Sulemana Sulemana; Nurainun Nurainun; Afriani Afriani (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2024)
This study applies the Project Based Learning (PjBL) learning model to the Pancasila subject of class X students at SMK Mega Link Majene. PjBL is an innovative learning that is centered on students and places teachers as motivators and facilitators, where students are given the opportunity to work autonomously to construct what they want to learn. This study aims to produce a collaborative project between students and PKn teachers in making films. This type of research is Research and Development (RnD) by applying the 4D model (Define, Design, Develop, Disseminate). The research instruments are (1) a test to assess the results of the film project. (2) teacher observation sheets to observe the practice of implementing PjBL in making films. (3) student observation sheets to observe student activities during the film making project process (4) Response questionnaires to the PjBL learning model in the film making project. Based on the research results, the process of determining the film was obtained, namely problem recognition, designing project planning, compiling a project schedule, project implementation and monitoring, project presentation, and evaluation and reflection. The data collected in this study are (1) Expert Validation Result Data; the distribution of the film project design development prototype was carried out complete with an assessment rubric, student reflection sheets, and teacher reflection sheets. (2) Learning outcome data in this case is the value of the film project that has been worked on by students with 5 stages of assessment, namely orientation/problem recognition, film project planning design, film project schedule preparation, film project implementation and monitoring, film project presentation, and evaluation and reflection. (3) Student activity data using observation sheets to observe students working on film projects. (4) Learning implementation data using teacher observation sheets to assess teacher implementation in implementing PjBL. (5) Student response data using questionnaires and given at the end of film project learning.